2020
DOI: 10.1111/1758-2229.12867
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the taxonomic diversity and molecular mechanisms of bacterial Mn(III) reduction

Abstract: Summary Soluble ligand‐bound Mn(III) can support anaerobic microbial respiration in diverse aquatic environments. Thus far, Mn(III) reduction has only been associated with certain Gammaproteobacteria. Here, we characterized microbial communities enriched from Mn‐replete sediments of Lake Matano, Indonesia. Our results provide the first evidence for the biological reduction of soluble Mn(III) outside the Gammaproteobacteria. Metagenome assembly and binning revealed a novel betaproteobacterium, which we designat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Sediment had been diluted over 1000‐fold by the time DNA was extracted for sequencing. Details on metagenomes from 395‐day anoxic enrichments of Lake Matano sediment incubated with Mn(III) pyrophosphate are reported in a separate publication (Szeinbaum et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Sediment had been diluted over 1000‐fold by the time DNA was extracted for sequencing. Details on metagenomes from 395‐day anoxic enrichments of Lake Matano sediment incubated with Mn(III) pyrophosphate are reported in a separate publication (Szeinbaum et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…However, in the natural environment with a complex microbial community and harsh conditions, such as aqueous, edaphic, and sedimentary environments, the most widespread electron acceptors is the iron-manganese mineral. , The slightly soluble Fe­(III) citrate was used as the terminal electron acceptor in the anaerobic sludge mixed bacteria to test the general applicability in practice. Microorganisms were observed to connect with Fe­(III) citrate via microbial nanowires.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Although this process has been well-studied, e.g., ( Nealson et al, 1988 ; Tebo et al, 2004 ; Hansel, 2017 ), it was only recently shown that a microorganism can catalyze Mn 2+ oxidation to gain energy ( Yu and Leadbetter, 2020 ). It has also been demonstrated that microorganisms can reduce aqueous ligand-bound Mn(III) ( Kostka et al, 1995 ; Szeinbaum et al, 2014 , 2017 , 2020 ) and solid-phase Mn(III), in the form of manganite (MnOOH) ( Larsen et al, 1998 ; Fredrickson et al, 2002 ), to provide energy for microorganisms.…”
Section: Introductionmentioning
confidence: 99%